Customer Satisfaction on Digital Banking Services: Evidence from Islamic Financial Institutions in Sri Lanka - Ahamed Hilmy, Hayathu Mohamed; Saujan, Iqbal (Journal of Islamic Economic Laws, 2025)
In the fast-paced modern era, time is crucial. Consumers with hectic schedules prefer smart solutions that enhance convenience and timeliness in financial activities. Traditional bank hours often conflict with busy schedules, but digital banking resolves this issue. Digital banking allows customers to use mobile phones and computers to check balances and conduct banking, offering more flexibility. This study aims to determine customer satisfaction with the digital banking services of Islamic financial institutions in Sri Lanka. The ISO 9000 standard E-SERVQUAL model and the digital service quality of Islamic financial institutions are analysed. Two hundred questionnaires were administered to customers with Amana Bank PLC and AL Adalah accounts. The research objective is a quantitative investigation to explore the relationship between independent and dependent variables within a given population. This study utilised the Statistical Product for Social Solutions version 20 (SPSS v. 20) for data analysis, employing descriptive analysis methods. For clarity, the results were displayed in bar graphs and pie charts using Microsoft Excel. The study evaluated service quality factors using Pearson correlation to examine the relationship between customer satisfaction (dependent variable) and independent variables (Efficiency, system availability, Ease of use, privacy, responsiveness).